Предмет: Алгебра,
автор: valeraerm
Преобразуйте выражение, используя формулы сокращённого умножения :
1. (2ab+3b)^2
2. (a-2b)^2
3. a-4
4. (√2-√3)(√2+√3)
5. (√2-√5)^2
Ответы
Автор ответа:
0
(2ab+3b)²=4a²b²+12b²a+9b²
(a-2b)²=a²-4ab+4b²
a-4
(√2-√3)(√2+√3)=(√2)²-(√3)²=2-3=-1
(√2-√5)²=(√2)²-2√5*√2+(√5)²=7-2√10
(a-2b)²=a²-4ab+4b²
a-4
(√2-√3)(√2+√3)=(√2)²-(√3)²=2-3=-1
(√2-√5)²=(√2)²-2√5*√2+(√5)²=7-2√10
Похожие вопросы
Предмет: Геометрия,
автор: Ananasik290
Предмет: Русский язык,
автор: nastya89021
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: Юлия3456
Предмет: История,
автор: Аноним